Mutational Analysis of the GXXXG/A Motifs in the Human Na+/Taurocholate Co-Transporting Polypeptide NTCP on Its Bile Acid Transport Function and Hepatitis B/D Virus Receptor Function - Palatini, Massimo; Müller, Simon Franz; Lowjaga, Kira Alessandra Alicia Theresa; Noppes, Saskia; Alber, Jörg; Lehmann, Felix; Goldmann, Nora; Glebe, Dieter; Geyer, Joachim (Frontiers in Molecular Biosciences, 2021)
Homodimerization is essential for plasma membrane sorting of the liver bile acid transporter NTCP and its function as hepatitis B/D Virus (HBV/HDV) receptor. However, the protein domains involved in NTCP dimerization are unknown. NTCP bears two potential GXXXG/A dimerization motifs in its transmembrane domains (TMDs) 2 and 7. The present study aimed to analyze the role of these GXXXG/A motifs for the sorting, function, and dimerization of NTCP. The NTCP mutants G60LXXXA64L (TMD2), G233LXXXG237L (TMD7) and a double mutant were generated and analyzed for their interaction with wild-type NTCP using a membrane-based yeast-two hybrid system (MYTH) and co-immunoprecipitation (co-IP). In the MYTH system, the TMD2 and TMD7 mutants showed significantly lower interaction with the wild-type NTCP. In transfected HEK293 cells, membrane expression and bile acid transport activity were slightly reduced for the TMD2 mutant but were completely abolished for the TMD7 and the TMD2/7 mutants, while co-IP experiments still showed intact protein-protein interactions. Susceptibility for in vitro HBV infection in transfected HepG2 cells was reduced to 50% for the TMD2 mutant, while the TMD7 mutant was not susceptible for HBV infection at all. We conclude that the GXXXG/A motifs in TMD2 and even more pronounced in TMD7 are important for proper folding and sorting of NTCP, and so indirectly affect glycosylation, homodimerization, and bile acid transport of NTCP, as well as its HBV/HDV receptor function.